Implementation Project Citizen Model Based on Pop-Up Books in Civics Education Learning - Pipid Mupidin; Dadang Sundawa; Iim Siti Masyitoh (PAEDAGOGIA, 2024)
The purpose of this research is to determine the effect of learning models. Project Citizen is based on a Pop-up Book on students' critical and creative thinking abilities in Civics subjects. This type of research is quantitative research in the form of a Pre-Experimental Design with a group Pretest-Posttest type. The sample for this research was 12th grade MIPA 2 students at SMA Pasundan 2 Cimahi City, totaling 32 students. Two types of instruments were used in this research, including observation sheets and critical and creative thinking skills tests. Validity test uses Pearson correlation and reliability testing using Cronbach's alpha. The research results show that Project Citizen's learning model is based on a Pop-up Book on students' critical and creative thinking abilities.